(untitled) (Economic and Political Thought, 2012)
The article presents challenges and tasks of human capital market for national education systems resulting in student mobility, increased participation and the need for standards and comparability of qualifications. Moreover, the author discusses the example of the United Kingdom, which can also refer to the situation in other countries, and he states that the achievement of minimum standards is no longer sufficient for the British universities because they need higher and higher standards in order to continue attracting foreign students who pay full fees, which the universities depend on as they constitute a considerable part of their finances.